2021
DOI: 10.1186/s12889-021-12339-7
|View full text |Cite
|
Sign up to set email alerts
|

Agenda-setting of tobacco control policy in Iran: a retrospective policy analysis study

Abstract: Background The prevalence of tobacco use, especially hookah, has increased in Iran In recent years, particularly among young people and women, and the age of onset of use has decreased. Tobacco use is the fourth leading risk factor for non-communicable diseases in Iran. These issues cause concerns in the country and led to the present study on tobacco control agenda-setting in Iran over a 30-year timeframe. Methods We conducted this retrospective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Different NGOs, such as the Iranian Anti-Tobacco Association, are actively involved in tobacco control initiatives in Iran, with a focus on public health and environmental protection [ 25 , 26 ]. The Iranian government, through the National Tobacco Control Headquarters supported by the government and monitored by the Ministry of Health and Medical Education, cooperates with relevant ministries, authorities, and NGOs [ 27 ]. The National Tobacco Free Initiative Committee (NTFIC) has actively cooperated and transferred information between the government and NGOs to speed up tobacco control endeavors in Iran [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different NGOs, such as the Iranian Anti-Tobacco Association, are actively involved in tobacco control initiatives in Iran, with a focus on public health and environmental protection [ 25 , 26 ]. The Iranian government, through the National Tobacco Control Headquarters supported by the government and monitored by the Ministry of Health and Medical Education, cooperates with relevant ministries, authorities, and NGOs [ 27 ]. The National Tobacco Free Initiative Committee (NTFIC) has actively cooperated and transferred information between the government and NGOs to speed up tobacco control endeavors in Iran [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second part consisted of the Safety Attitude Questionnaire (SAQ), which was designed by Sexton et al (16). The reliability and validity of its Persian version were confirmed by Tourani et al by calculating Cronbach's alpha coefficient of 86% (17). The goodness-of-fit index from the CFA showed a well-founded model fit (CFI=0.8, ECVI=0.8, and RMSEA=0.02) for the SAQ tool (18).…”
Section: Methodsmentioning
confidence: 99%
“…5 6 In recent years, smoking prevalence in Iran has also increased, especially among youth and women, and smoking ages have decreased. 7 A meta-analysis found that the smoking prevalence of students in Iran was 7.9%. 10.6% of men and 4.5% of women were smokers.…”
Section: Introductionmentioning
confidence: 99%